Physical Workload and Work Fatigue among Tank Car Drivers at Surabaya Integrated Terminal - Milinia, Tasya Endah; Haq, Dani Nasirul; Alia, Siti Arum (Folia Medica Indonesiana, 2022)
Highlights: • Physical workload had no correlation with work fatigue among tank car drivers. • Companies and tank car drivers are advised to carry out work fatigue management by exercising lightly and fulfilling nutritional and water intake. Abstract : Every year, there are nearly a thousand times more of non-fatal accidents than fatal accidents. In Indonesia, Java Island has the highest number of traffic accidents. Work accidents have three main factors, i.e. worker factors, labor factors, and environmental factors. Fatigue is one of the conditions called silent killer. The aim of this research was to analyze the correlation of physical workload with work fatigue in tank car drivers at Surabaya Integrated Terminal. This research was an observational cross-sectional study. The sample were 205 tank car drivers fufilling the inclusion criteria as fuel tank car drivers and willing to participate in this research. The independent variable in the study was physical workload, while the dependent variable was subjective work fatigue. Data were collected using the IFRC questionnaire. The Spearman's correlation test revealed the value of Sig. (2-tailed)=0.437, indicating no significant correlation between physical workload and subjective work fatigue. The results showed that the physical workload had no correlation with work fatigue. Fatigue found among the drivers are probably induced by other factors not analyzed in this study. Companies and tank car drivers are advised to carry out work fatigue management by, for example, drinking water regularly, carrying out light exercise, and fulfilling nutritional intake.